THE LANGUAGE ACQUISITION IN BILINGUAL CHILDREN: A STUDY OF A 3-YEAR-OLD - Al Anwar, Sylvia Febbryani; Istama, Nanda Rizka; Fauzi, Unzila Alzura; Nargis (Media Inovasi Pendidikan dan Publikasi, 2024)
This study examines language acquisition in early childhood, with a focus on Bebi, a 3-year-old bilingual child. The aim of this research is to understand the language acquisition process of Bebi, who is a bilingual child, and how he combines vocabulary from two different languages ​​in everyday communication. The research method used is descriptive qualitative, with data collection through observation of daily interactions between children and their environment. The research results show that Bebi tends to simplify words that are difficult to pronounce and uses pronunciation patterns that are already familiar to her. Children also demonstrate a basic understanding of everyday concepts and objects. These findings suggest that bilingual environments can influence children's language development in unique ways, and that bilingual children can master both languages ​​well if they get enough exposure.